Expert System For Determining Composition Of Replacement Feed At The Time Of Raw Materials In Cow Fatting Companies With Backward Chaining Inference Case Study : ( PT. Andini Agro Loka, Central Lampung) - Pakarti Riswanto; Herman Affandi; Sidik Rahmatullah (Proceeding International Conference on Information Technology and Business, 2019)
In the business of fattening cattle, cow feed nutrition is very supportive in the success of this business. But cattle farmers' understanding of the composition of feed nutrition is still low. In the business of fattening cattle, cow feed nutrition is very supportive in the success of this business. But cattle farmers' understanding of the composition of feed nutrition is still low.This expert system can be used as information and guidelines for determining nutrient composition in cattle feed using Backward Chaining. This method uses a chain that is crossed from a hypothesis back to facts that support the hypothesis. The use of this system can provide accurate information and references for users in the form of determining the nutritional composition of cattle feed. This system can provide assistance in the form of determining the composition of feed replacement during the lean season using raw material backward chaining by not reducing the nutritional value contained in the feed and the price remains economical.Key words: cow feed nutrition, expert systems, and backward chaining